Sulfate optimization in ettringite rich cements by SO3/Al2O3 molar ratio: A comparative study of calcium sulfoaluminate and aluminate cements - Huaqiang Sun; Tianzhu Lin; Kanghong Zhuo; Jueshi Qian; Xiangsheng Chen; Jian Zhang; Yubo Sun (Case Studies in Construction Materials, 2024)
The hydration process of calcium sulfoaluminate (CSA) and aluminate cement (CAC) is influenced by their composition and calcium sulfate sources. Increasing the calcium sulfate content promotes ettringite generation; however, exceeding the optimal threshold may cause volume instability. This study aims to optimize sulfate levels in CSA and CAC by adjusting the SO3/Al2O3 molar ratios. Contour maps were used to analyze how different sulfate sources and calcium sulfate levels affect strength development, ettringite formation, and volume stability. Both gypsum and anhydrite similarly improved compressive strength in CAC and CSA at equivalent SO3/Al2O3 ratios. However, gypsum caused more significant expansion than anhydrite at equivalent SO3/Al2O3 ratios, as indicated by the higher expansion values in gypsum-rich regions. The SO3/Al2O3 molar ratio is crucial for regulating ettringite formation, enhancing compressive strength, and ensuring volume stability in CSA and CAC systems. Maintaining this ratio below 1.0 enabled the addition of sufficient calcium sulfate to achieve optimal performance.